Peran Guru dalam Pencegahan Bullying di PAUD - andini dwi arumsari; Dedi Setyawan; Rellista Yulianti Putri; Ria Rahmawati (MOTORIC, 2019)
Bullying is social behaviour that commonly happened in educational environment. Bullying involves student as the actor, victim, and bystander. This behaviour stimulates various negative impacts not only for victim but also the actor. When bullying happens in early childhood education, educator plays essential role to recognise, identify, and prevent it. The present study aims to elaborate the important of educator role in preventing bullying that may occur in early childhood education. The present study uses literature review in order to gain information that are related to bullying in early childhood education. moreover, the present study also conducts interview with various educators to gain valid data regarding this behaviour. The present study shows that educators recognise violent acts that are conducted by their student but unfortunately they are not able to identify whether those actions can be determined as bullying toward early childhood children. Moreover, this violent action is a stimulus which can lead a children in conducting juvenile delinquency in the near future for the actor. Therefore, early childhood educator holds essential role in preventing bullying acts for early childhood children in order to prevent this behaviour becomes a habit.